Hypnotherapy Intervention To Reduce Cigarette Consumption Habits In Adolescent Children: Literature Review - Syahrizal, Rofi; Sari, Anna Juwita Puspita; Sari, Vina Amelia Tunnikmah Desya Cournia (Griya Eka Sejahtera, 2024)
Background: The habit of smoking in adolescents is indeed a problem that needs special attention, considering the impact on health where lung function will experience impaired development. The social aspect of smoking behavior for adolescents can cause adverse effects for passive smokers because the risks borne by passive smokers are more dangerous than active smokers.Methods: The research design in this article is a literature review, by searching several literature sources in the form of research journals using databases such as: Ebsco Host, PubMed, Google Schoolar, elsevier, and Springer. By using the search keywords: Hypnotherapy, smoking, and adolescents. The year limitation used is from 2020 to 2024. The language used is Indonesian and English, free journals are not paid.Results: Based on the results of the research that has been carried out, hypnotherapy intervention has an influence on reducing smoking consumption habits in adolescent children.Conclusion: Based on the results of the study, hypnotherapy intervention shows the benefits in changing the subconscious of adolescents to stop or reduce the habit of consuming cigarettes